Estimation of developed reserves in gas lifted wells. (2009)
Reliable estimates of petroleum reserves are invaluable in reservoir management decisions and economic evaluation. Classical decline curve analysis techniques have been routinely used and are generally accepted in the industry to reliably estimate developed reserves up to a predetermined economic limit qec in oil wells. However Decline curve analysis techniques are based on the assumption that past production trends and their controlling factors will continue in the future and therefore can be extrapolated for predictions. During gas lifting, production trends could be distorted hence there is need to modify the classical decline curve analysis equation. In this study, the principle of superposition has been applied to the entire duration of production (t) of wells producing under gas lift. This resulted in the so called Double Semi log equation for well decline analysis. Model validation with two fields in the Niger Delta area show excellent results and the economic advantage of gas lifting. The Models showed excellent correlation coefficients with available field data. It is concluded that gas lift could increase the reserves in some wells. Furthermore the Double Semi log technique provides a better and more reliable theoretical foundation, easier and more reliable technique for decline analysis in gas lifted wells.